If I stay : a novel - Forman, Gayle (New York : Dutton Books, 2009)
While in a coma following an automobile accident that killed her parents and younger brother, seventeen-year-old Mia, a gifted cellist, weighs whether to live with her grief or join her family in death.
Sequel: Where she went.
Biblioteca Preparatoria.
Keywords: Coma -- Fiction; Death -- Fiction; Medical care -- Fiction; Cello -- Fiction; Musicians -- Fiction; Family life -- Oregon -- Fiction; Oregon -- Fiction